KEPEMIMPINAN KEPALA SEKOLAH DALAM MELAKUKAN INOVASI MANAJEMEN PENDIDIKAN DI MAS BUSTANUL MUBTADI’IN PROPPO PAMEKASAN - Sahibudin Sahibudin (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2019)
In the current era of globalization, education is one of the obligations that must be taken by personal and social that can not be negotiable. Because basically education is a social process that aims to develop the potential of human life in order to face the demands of the age in the future, along with the development and changing times that are increasingly shifting. Educational management is the study of how to organize resources to achieve goals that have been set productively and how to create a good atmosphere for people who participate in achieving agreed goals. In relation to the development of education, the principal has a very important role and task. This is because the principal as a leader is one of the factors that drives the progress of the world of education. This means that school principals are required to have the ability to carry out educational innovations that are no longer relevant to current conditions for the achievement of national and state development.